Caring for the person with cancer: Information and support needs and the role of technology. Issue 6 (20th April 2018) - Heynsbergh, Natalie; Botti, Mari; Heckel, Leila; Livingston, Patricia M.
Abstract: Objective: Informal carers experience a variety of information and support needs when providing care to someone with cancer. It is unclear when carers seek information and what resources they access to support themselves throughout the cancer trajectory. Methods: A sample of 45 carers and 15 oncology nurses were recruited to participate in either focus groups or phone interviews. Results: Carers in the study were more likely to be women (60%), caring for a spouse or partner (64.4%), living with the patient (86.7%), and hold a university degree (46.7%). The majority of oncology nurses were females (66.6%). Findings showed that carers had limited access to adequate information as needs arose. Supports used to address information needs included information booklets, the Internet, and communication with healthcare professionals or with other carers. Barriers in communication between nurses and carers impacted on the adequacy of information received. Participants reported that technology, such as smartphone applications, might be appropriate for improving information and support needs. Conclusions: Caring for someone with cancer is multifaceted. Carers need access to timely information to help them effectively manage patients' needs. Future studies should assess the role of contemporary approaches, such as digital technology, as a solution to the delivery of information and support for carers of people with cancer.